2012
DOI: 10.1002/cne.23160
|View full text |Cite
|
Sign up to set email alerts
|

Area‐specific substratification of deep layer neurons in the rat cortex

Abstract: Gene markers are useful tools to identify cell types for fine mapping of neuronal circuits. Here we report area-specific sublamina structure of the rat cerebral cortex using cholecystokinin (cck) and purkinje cell protein4 (pcp4) mRNAs as the markers for excitatory neuron subtypes in layers 5 and 6. We found a segregated expression, especially pronounced in layer 6, where corticothalamic and corticocortical projecting neurons reside. To examine the relationship between gene expression and projection target, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 65 publications
5
23
0
Order By: Relevance
“…The present results also reveal differences in cellular density between the two layers, as well as the presence of geniculate terminations throughout 6A but not 6B. Prior reports of V1 lamination largely consider layer 6 as a single layer that blends into the ventral white matter (Lund, 1973; Lund et al, 1988; Casagrande and Kaas, 1994), but subtle differences between upper and lower tier cells in this layer have been considered (Levitt et al, 1996; Yamamori and Rockland, 2006; Watakabe et al, 2012, 2006). Our results, in combination with recent studies of layer- and cellular-specific gene expression, suggest that layer 6 is made up of two functional subdivisions; a superficial sublayer with sparse geniculate inputs as well as intrinsic and extrinsic visual projections, and a deep sublayer with separate inputs and functions.…”
Section: Discussionsupporting
confidence: 52%
“…The present results also reveal differences in cellular density between the two layers, as well as the presence of geniculate terminations throughout 6A but not 6B. Prior reports of V1 lamination largely consider layer 6 as a single layer that blends into the ventral white matter (Lund, 1973; Lund et al, 1988; Casagrande and Kaas, 1994), but subtle differences between upper and lower tier cells in this layer have been considered (Levitt et al, 1996; Yamamori and Rockland, 2006; Watakabe et al, 2012, 2006). Our results, in combination with recent studies of layer- and cellular-specific gene expression, suggest that layer 6 is made up of two functional subdivisions; a superficial sublayer with sparse geniculate inputs as well as intrinsic and extrinsic visual projections, and a deep sublayer with separate inputs and functions.…”
Section: Discussionsupporting
confidence: 52%
“…By double ISH, we found that the nurr1 + neurons in both mouse and macaque claustrum co-express VGluT1 mRNA (Figure 4 and data not shown). (2) In our previous study, moreover, we reported that excitatory neurons in layer 6 of rats can be classified as either pcp4 + or cck + cells, and that nurr1 + cells express cck mRNA (Watakabe et al, 2012). In both rodents and monkeys, cck mRNA was expressed in the claustrum but not in the striatum (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…The FastBlue injection and the subsequent ISH were performed as previously (Watakabe et al, 2007). The FluoroGold injection and the following ISH was performed as previously (Watakabe et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…These tracers, largely fluorescent, can be used to map the connections emerging from an area of interest or the regions projecting onto the region of interest. This approach, recently utilized in the mouse (Wang et al, 2011) and the rat (Watakabe et al, 2012), can be combined with 3D modeling to provide details on the functional relationship between areas. Additionally, these paradigms can also be applied in developmental studies to determine when areas become wired together and therefore the relative hierarchy of individual areas (e.g., the establishment of thalamocortical connections in the mouse) (Little et al, 2009; Deck et al, 2013).…”
Section: How Are Visual Cortical Areas Defined?mentioning
confidence: 99%